Epidemiology of necrotizing infection caused by Staphylococcus aureus and Streptococcus pyogenes at an Iowa hospital - Dipendra Thapaliya; Ashley M. O'Brien; Shylo E. Wardyn; Tara C. Smith (Elsevier, 2015)
Summary: The present study was performed to characterize the epidemiology of necrotizing soft tissue infection caused by Streptococcus pyogenes (n = 14) and Staphylococcus aureus (n = 14) isolates collected at the University of Iowa Hospitals and Clinics. An additional 9 S. pyogenes isolates were collected from patients being treated for mild respiratory infections and served as a comparison sample in the analysis. Patient data corresponding to the isolates (n = 37) were also collected in order to identify risk factors or comorbid conditions possibly correlated with necrotizing fasciitis (NF). The prevalence of methicillin-resistant S. aureus among the study isolates was 35.7% (5/14), and the prevalence of the Panton-Valentine leukocidin (PVL) gene was 57% (8/14). The S. pyogenes NF (wound) isolates (n = 14) belonged to 10 different emm types, none of which appeared to be associated with more severe disease when compared to the milder infection (throat) samples (n = 9). Comorbid conditions such as diabetes and cardiovascular disease were significantly associated with NF. The results indicate that there may be a high prevalence of the PVL virulence factor in NF infections and that spa type t008 may be responsible for the increasing incidence of S. aureus NF infections in Iowa. Keywords: Staphylococcus aureus, Streptococcus pyogenes, Necrotizing fasciitis, Epidemiology, Infection